Caries prevalence in chronic alcoholics and the relationship to salivary flow rate and pH - Dukić, Walter; Dobrijević, Tanja Trivanović; Katunarić, Marina; Lesić, Stjepanka (Central European Journal of Public Health, 2013)
AIM: The aim of this study was to investigate the dental status of alcoholics; to evaluate the relationship of unstimulated and stimulated saliva pH on their decayed/missing/filled teeth (DMFT); and to evaluate the relationship of unstimulated and stimulated salivary flow rate on their DMFT. METHOD: A cross-sectional study was conducted in patients treated for alcohol dependency (n = 70; mean age 41.7 years) and a control group of non-alcoholics (n = 70; mean age 39.1 years). Examinations for dental caries were conducted using the World Health Organization (WHO) criteria and questionnaires. The correlation between nominal variables was determined using chi2 test (alpha = 0.05). The correlation between interval variables was determined using Pearson's correlation coefficient. RESULT: The mean DMFT was similar in alcoholics (14.40) and the control group (13.44) (p > 0.05). There was a statistically significant correlation between alcoholism and unstimulated salivary flow rate (p < 0.05), but no relationship on DMFT was recorded. No statistically significant differences were found between alcoholics and controls in terms of stimulated salivary flow rate (p > 0.05) or stimulated salivary flow on DMFT (p > 0.05). There was a statistically significant correlation between alcoholism and the pH value of stimulated saliva (p < 0.01). There was no correlation between the amount of alcohol consumed and the number of carious lesions (p > 0.05). CONCLUSIONS: No major differences were found with respect to overall DMFT in alcoholics compared to the control group. Alcoholism and stimulated salivary flow rate showed no correlation. Unstimulated salivary flow rate as well as the pH values of both unstimulated and stimulated saliva, were lower in the alcoholic group.
Keywords: Humans; Dental Caries; lidé; sliny; Female; lidé středního věku; Chorvatsko; Male; Saliva; průřezové studie; Croatia; Adult; dospělí; Alcoholism; Cross-Sectional Studies; zubní kaz; Middle Aged; ženské pohlaví; mužské pohlaví; alkoholismus